Psychometric Properties of Social Support Questionnaire to Measure Empowerment in Elderly Patients with Cardiovascular Disease in Iran - Maryam Musavinasab; Maryam Ravanipour; Shahnaz Pouladi; Niloofar Motamed (Mashhad University of Medical Sciences, 2018)
Background: Chronic diseases and functional decline can affect empowerment among the elderly in the lifestyle management to benefit from social support. Aim: The aim of the present study was to determine the psychometric properties of Social Support Questionnaire to measure empowerment in elderly patients with cardiovascular disease in Iran. Method: This study was conducted on 250 elderly patients with cardiovascular disease referring to the medical centers of Bushehr city, Iran, using the convenience sampling method. Results: Content validity index and content validity ratio were calculated as 0.94 and 0.96 respectively. Based on the exploratory factor analysis, the number of the questionnaire items was reduced to 23 items. Empowerment was classified under seven factors. The internal and external reliabilities of the questionnaire were estimated as 0.85 and 0.83, respectively. Implications for Practice: The final questionnaire had appropriate psychometric properties and strength of factor structure. Therefore, this tool can be used by the healthcare providers in the health care systems of Iran.